Integrating Maqasid al-Shariah in the e-Procurement System: A Governance Framework for Shariah Compliance in Malaysia's Public Sector (Architecture Image Studies, 2025)
The Malaysian government’s development of an e-procurement system, a key component of its broader e-government initiative, aims to enhance the efficiency, transparency, and accountability of public sector supply chain management. While the technological aspects of this system are essential, the integration of Maqasid al-Shariah (the objectives of Sharia law) within the system is crucial for ensuring ethical governance. This paper explores the incorporation of Maqasid al-Shariah within Malaysia's e-procurement framework, positioning it as a central element of the Malaysia Shariah Index Model (ISM). The ISM serves both as a governance model and a tool for assessing Sharia compliance in government procurement processes. The study reveals that embedding Maqasid al-Shariah within the e-procurement system promotes ethical procurement practices, ensuring decisions align with Islamic principles of justice, equity, and fairness, thereby reducing corruption and inefficiencies. Through interviews with seven key informants, including policymakers, procurement specialists, and Sharia experts, the research highlights both the successes and challenges faced during the integration of Maqasid al-Shariah in public procurement. Key findings suggest that the Maqasid al-Shariah framework significantly enhances transparency, accountability, and fairness, fostering a reduction in procurement-related fraud and corruption. However, challenges such as the lack of consistent Sharia expertise, resistance to change within procurement culture, and technological inefficiencies remain prevalent. The study also proposes several policy recommendations to strengthen Sharia compliance, including capacity building for procurement officials, strengthening Sharia oversight, and ensuring regular system upgrades. This paper contributes to understanding how Islamic governance principles can be operationalized within modern public sector procurement systems, ensuring both operational efficiency and adherence to Sharia law. Ultimately, the integration of Maqasid al-Shariah within Malaysia’s e-procurement system represents a transformative step towards ethical governance and the sustainable development of the public sector.